Analisis Pelaksanaan Kebijakan Manajemen Berbasis Sekolah dalam Peningkatan Mutu Pendidikan di SMPN 2 V Koto Timur Padang Alai Pariaman - Handri Adi (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2017)
This research was designed and analyzed by qualitative descriptive. The data analyzed by comparative analysis. Based on the research can be concluded that implementation MBS of SMPN 2 V Koto Timur Padang Alai by several steps, there are: determine of the work program, socialization, increasing the partnerships or relation, applying the of good governance principles, improving the capacity, authority distribution and responsibility, participation community, openness and accountability, cooperation, oriented to the graduates and the availability of infrastructure.